Penggunaan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa SDIT Denada - Dianis Safitri; Alberth Supriyanto Manurung (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was conducted in class V SDIT Denada with a total of 20 students in the odd semester of the 2019/2020 school year. This research procedure went through two cycles, where each cycle consisted of (1) the planning stage, (2) the action stage, (3) the observation stage, (4) the reflection stage. Data collection in the study used student learning activity observation sheets, teacher activity observation sheets in using problem-based learning models, test questions to measure student learning outcomes on the conversion material for units of speed and volume. The data analysis technique in this research is qualitative and quantitative analysis. The results showed that the use of problem-based learning models in the conversion material for units of speed and volume could improve student learning outcomes at SDIT Denada. These results can be seen from the learning outcomes of students in cycle I with an average value of 70.8 with a percentage of 60% while in cycle II the average value is 75.15 with a percentage of 85%. The average value of student learning activities in cycle I (50%) , in cycle II (83%) and there was an increase (33%).